2019
DOI: 10.1126/science.aaw7733
|View full text |Cite
|
Sign up to set email alerts
|

IFITM proteins inhibit placental syncytiotrophoblast formation and promote fetal demise

Abstract: Placenta formation and fetal demise A critical step of placental development is the fusion of trophoblast cells into a multi-nucleated syncytiotrophoblast layer. Trophoblast fusion is mediated by syncytins, encoded by endogenous retrovirus–derived envelope glycoproteins. Buchrieser et al. report that interferon-induced transmembrane (IFITM) proteins inhibit syncytin-mediated syncytiotrophoblast formation, restricting placental development and triggering fetal demi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 35 publications
5
55
0
2
Order By: Relevance
“…A very interesting study showed that placental damage and abortion caused by the virus-induced upregulation of type I IFN during pregnancy is associated with the palmitoylation of IFITM3. This can be caused by the mutation in three cysteine residues of IFITM3, which suppresses the inhibition of cell fusion (Buchrieser et al, 2019). In one of our studies, we confirmed that resistance to the Japanese encephalitis virus (JEV) infection requires the S-palmitoylation modification of IFITM in swine (Xu et al, 2020).…”
Section: Palmitoylation Of Host Cell Proteinssupporting
confidence: 71%
See 1 more Smart Citation
“…A very interesting study showed that placental damage and abortion caused by the virus-induced upregulation of type I IFN during pregnancy is associated with the palmitoylation of IFITM3. This can be caused by the mutation in three cysteine residues of IFITM3, which suppresses the inhibition of cell fusion (Buchrieser et al, 2019). In one of our studies, we confirmed that resistance to the Japanese encephalitis virus (JEV) infection requires the S-palmitoylation modification of IFITM in swine (Xu et al, 2020).…”
Section: Palmitoylation Of Host Cell Proteinssupporting
confidence: 71%
“…This fusion complex is then trafficked to the lysosome, which relies on the palmitoylation of Grantham et al, 2009;Thaa et al, 2011;Thaa et al, 2012;Veit and Siche, 2015;Ekanayake et al, 2016;Manzoor et al, 2017;Su et al, 2018) HA Type I glycoproteins 3 (Melkonian et al, 1999;Kordyukova et al, 2008;Engel et al, 2010;McBride and Machamer, 2010;Kordyukova et al, 2011;Brett et al, 2014;Chlanda et al, 2017; its three conserved cysteines at 70,71, and 105 sites (Spence et al, 2019). Furthermore, preventing the fusion of the viral membrane with the cells or the fusion among the infected cells could be the main antiviral mechanism of IFITM (Buchrieser et al, 2019;Zani et al, 2019). A very interesting study showed that placental damage and abortion caused by the virus-induced upregulation of type I IFN during pregnancy is associated with the palmitoylation of IFITM3.…”
Section: Palmitoylation Of Host Cell Proteinsmentioning
confidence: 99%
“…Although a recent study revealed that a high level of IFITM expression could inhibit the fusion of trophoblast cells for syncytiotrophoblast formation, the IFITMs did not alter growth of placental trophoblast cells already formed. 41 In the present study, we applied escalating doses to 3 times the therapeutic dose of IFITM3-Exos to determine the safety of IFITM3 to the placenta and the fetuses and did not observe any placental lesions or fetal reduction, demonstrating the in vivo safety of IFITM3-Exos.…”
Section: Discussionmentioning
confidence: 62%
“…The primers used for sequencing and the site‐directed mutagenesis are listed in the tables␣(Tables EV1 and EV2 ). pQCXIP‐Empty control plasmid, pQCXIP‐IFITM1‐N‐FLAG, pQCXIP‐IFITM2‐N‐FLAG, pQCXIP‐IFITM3‐N‐FLAG were previously described (Buchrieser et␣al , 2019 ). pQCXIP‐BSR‐GFP11 and pQCXIP‐GFP1‐10 were from Yutaka Hata ((Kodaka et␣al , 2015 ); Addgene plasmid #68716; http://n2t.net/addgene:68716 ; RRID: Addgene_68716 and Addgene plasmid #68715; http://n2t.net/addgene:68715 ; RRID: Addgene_68715).…”
Section: Methodsmentioning
confidence: 99%